Housing property rights, collateral, and entrepreneurship: Evidence from China - Fan, Gang-Zhi; Li, Han; Li, Jiangyi; Zhang, Jian (Journal of Banking & Finance, 2022)
This paper provides new evidence on the impact of the housing collateral lending channel on entrepreneurial activities by allowing homeowners to access property equity and invest in new businesses. We exploit dual housing property rights forms in China as an instrument, where complete access to collateral values is only legally granted to homeowners with full property rights (FPR), with no access for those without FPR. Using data from a large survey, we find that local house price growth significantly increases the probability of starting a new business for FPR homeowners relative to the control group. The effects are robust when we rely on the exogenous shock induced by the house purchase restriction and primarily driven by homeowners without household debt. Macro analysis supports a positive correlation between the concentration of FPR homeowners and employment and economic growth, where homeowners are better able to obtain external financing via the collateral channel.